The effect of wheat grains soaking by ethylene glycol in raising freezing torelance and effect in plants production - Mohammed Sadek; Nahla Hamouk (College of Education for Pure Sciences, 2005)
The study was carried out during the winter of 2002-2003, USlflg spring heal Triticitinaesliviun L, (Anu-(mnb-3-cultivar). Tlic study aimed to investigate the possibility of using ethyieneglyeol (an antifreezing solution) for induction of freezing tolerance in wheat plants by seeds soaking method. The stud was carried out in three replicates and designed as (4 < 5) factorial experiment according to randomize complete block design with two factors. The first factor was ethyieneglyeol concentrations which comprised lour levels (0, >. 1.0 and 20 %, sv), while the second factor comprised five periods of exposure to -5°c(0, 12, 24, 48 and 72 hrs). Differenl concentrations of ethyieneglyeol were led to significant increase in: plan! height at harvesting time; spikes weight; weight of J 000 grains, while, there were no significant effects in : no. of imernodes /plant; length of spikes; length of last imernodes; no. of tillers plant at harvesting time. no. of spikes plant and no. of grains/spikes. Different freezing periods led to significant decrease in ail mentioned parameters except in no. of internodes/plant and spikes length. All the interactions between the two factors were significant except no. of internodes plant, Analysis of regression between ethyieneglyeolconcenterations and exposure periods with all studied parameters were also done.